Autoregulation in Resistance Training for Lower Limb Tendinopathy: A Potential Method for Addressing Individual Factors, Intervention Issues, and Inadequate Outcomes - Burton, Ian (Frontiers in Physiology, 2021)
Musculoskeletal disorders, such as tendinopathy, are placing an increasing burden on society and health systems. Tendinopathy accounts for up to 30% of musculoskeletal disorders, with a high incidence in athletes and the general population. Although resistance training has shown short-term effectiveness in the treatment of lower limb tendinopathy, more comprehensive exercise protocols and progression methods are required due to poor long-term outcomes. The most common resistance training protocols are predetermined and standardized, which presents significant limitations. Current standardized protocols do not adhere to scientific resistance training principles, consider individual factors, or take the importance of individualized training into account. Resistance training programs in case of tendinopathy are currently not achieving the required intensity and dosage, leading to high recurrence rates. Therefore, better methods for individualizing and progressing resistance training are required to improve outcomes. One potential method is autoregulation, which allows individuals to progress training at their own rate, taking individual factors into account. Despite the finding of their effectiveness in increasing the strength of healthy athletes, autoregulation methods have not been investigated in case of tendinopathy. The purpose of this narrative review was 3-fold: firstly, to give an overview and a critical analysis of the individual factors involved in tendinopathy and current resistance training protocols and their limitations. Secondly, to give an overview of the history, methods, and application of autoregulation strategies both in sports performance and physiotherapy. Finally, a theoretical adaptation of a current tendinopathy resistance training protocol using autoregulation methods is presented, providing an example of how the method could be implemented in clinical practice or future research.